Increased bystander intervention when volunteer responders attend out-of-hospital cardiac arrest - Nielsen, Christian Gantzel; Folke, Fredrik; Andelius, Linn; Hansen, Carolina Malta; Væggemose, Ulla; Christensen, Erika Frischknecht; Torp-Pedersen, Christian; Ersbøll, Annette Kjær; Gregers, Mads Christian Tofte (Frontiers in Cardiovascular Medicine, 2022)
Aim: The primary aim was to investigate the association between alarm acceptance compared to no-acceptance by volunteer responders, bystander intervention and survival in out-of-hospital cardiac arrest. Methods: This retrospective observational study included all suspected OHCAs with activation of volunteer responders in the Capital Region of Denmark (November 1st, 2018 to May 14, 2019), the Central Denmark Region (November 1st, 2018 to December 31, 2020), and the Northern Denmark Region (February 14, 2020 to December 31, 2020). All OHCAs unwitnessed by EMS were analyzed on the basis on alarm acceptance and arrival before EMS. The primary outcomes were bystander cardio-pulmonary resuscitation (CPR), bystander defibrillation and secondary outcome was 30-day survival. A questionnaire sent to all volunteer responders was used with respect to their arrival status. Results: We identified 1,877 OHCAs with volunteer responder activation eligible for inclusion and 1,725 (91.9%) of these had at least one volunteer responder accepting the alarm (accepted). Of these, 1,355 (79%) reported arrival status whereof 883 (65%) arrived before EMS. When volunteer responders accepted the alarm and arrived before EMS, we found increased proportions and adjusted odds ratio for bystander CPR (94% vs 83%, 4.31 (95% CI [2.43 – 7.67]) and bystander defibrillation (13% vs 9%, 3.16 [1.60 – 6.25]) compared to cases where no volunteer responders accepted the alarm. Conclusion: We observed a 4-fold increased odds ratio for bystander CPR and a 3-fold increased odds ratio for bystander defibrillation when volunteer responders accepted the alarm and arrived before EMS.